Pedogamy in Neidium (Bacillariophyceae) - Poulícková, A (Folia microbiologica, 2008)
Single (unpaired) vegetative cells of freshwater pennate diatom Neidium cf. ampliatum differentiated into gametangia and produced a single zygote (auxospore) via a pedogamic process. The gametic nuclei fused after auxospore expansion had begun. The auxospore expanded in parallel to the apical axis of the gametangium.
Keywords: buněčné dělení; Spores; spory; Diatoms; Zygote; Fresh Water; sladká voda; Cell Differentiation; buněčná diferenciace; Cell Division; zygota; rozsivky